Analisis Postkolonial terhadap Perkataan Yesus Mengenai Perceraian dalam Matius 19:1-9 - Debora Retinawati Nababan; Elfrida Tampubolon; Prianus Mom (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
Analysis carried out after colonialism of what Jesus said about divorce in Matthew 19:1-9 shows how the text can be understood in the context of power and cultural domination. This research conducted qualitative research using a literature study approach. Researchers can use this research method to study, analyze and describe the meaning of Jesus' words regarding divorce through postcolonial analysis of Matthew 19:1–9 in Indonesian Christian understanding. This method considers how colonial beliefs and customs influenced the interpretation and application of Jesus' teachings on divorce. Jesus explained that divorce was not part of God's original plan, but was permitted by Moses because of the hardness of the human heart. Jesus then set a new, stricter standard: divorce was only permitted in cases of adultery.